Effect of nonsteroidal antiinflammatory agent on Sprague-Dawley rats liver glutathione S-transferases activity - Sudibyo Martono, Sudibyo Martono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Glutathion S-transferase (GST) is a group of multifunction isoenzymes playing a role as katalisator in releasing inflammatory mediators prostaglandin and leukotrien. Non-steroidal antiinflammatory drugs (NSAID) such as pentagamavunon-0 (Pgv-0), piroxicam, and mefenamic acid have antiinflammatory effect. Aim of study: The study was to know the effect of pentagamavunon-0 (Pgv-0), piroxicam and mefenamic acid on GST.Materials and methods: The effects of non-steroidal antiinflammatory drugs (NSAID.) piroxicam, mefenamic acid, and pentagamavunon-0 (Pgv-O) in vitro on mu and pi classes of Sprague-Dawley rats liver glutathione S-transferases (GST)-activity was studied. GST-activities was measured spectrophotometrically on the conjugation reaction between glutathione (GSH) and 1,2-dichloro-4-nitrobenzene (for representing the mu class of GST) or etachrynic acid (for representing the pi class of GST). The potency of inhibitory effect was stated as IC50 value (the concentration of inhibitor resulting in 50 % inhibition of GST-activity).Results: The result showed that piroxicam inhibited strongly the mu class of GST-activity with IC60 value of 42.66 mM and inhibited weakly the pi class of GST-activity with IC50 value of 100.79 mM. Mefenamic acid inhibited weakly the mu and pi classes of GST-activity with IC50 values of 107.09 and 275,0 mM (extrapolated), respectively. In this research, Pgv-0 was found to be the strongest inhibitor of the mu class of GST-activity with IC50 value of 3.91 mM and did not inhibit the pi class of rats liver GST-activity.Conclusions: Based on the results, it can be concluded that the three NSAIDs studied, all showed the inhibitory effects of mu class of GST-activity in decreasing order of Pgv-0, piroxicam, and mefenamic acid. Three of them did not or very weakly inhibited the pi class of rats liver GST-activity.Key words: NSAIDs - glutathione S-transferase - pentagamavunon-0 - 1,2-dikloro-4-nitrobenzene - etachrynic acid.Â